ISLAM DAN BUDAYA LOKAL - Hamzah, Saidin; Azis, Abdul; Faradilla (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the relevance of Islamic teachings to the values of local wisdom in the traditional expressions of the Bima people as an effort to strengthen Islamic identity and maintain social harmony. Using a descriptive qualitative method, the research was carried out through field studies and analysis of the meaning of traditional expressions contained in Nggusu Waru. The results of the study show that each expression contains values that are in harmony with Islamic teachings. such as, Maja Labo Dahu cultivates moral control through shame and fear; Ma Bae Ade instills empathy; Mambani Labo Disa affirmed courage; A man who has been patiently waiting for his or her to be patient; Ndinga Nggahi Rawi Pahu teaches consistency between speech and action; Ma Taho Hidi emphasizes life balance; Dou Ma Wara Di Woha Dou strengthens social solidarity; and Ntau Ro Wara underlined physical and spiritual well-being. These findings confirm that Islam and the local culture of Bima interact harmoniously and complement each other in shaping the social, spiritual, and cultural ethics of the community. This research emphasizes that the traditional expression Bima is a real manifestation of the integration of Islamic values and local wisdom in daily life. Penelitian ini bertujuan untuk menganalisis relevansi ajaran Islam dengan nilai-nilai kearifan lokal dalam ungkapan tradisional masyarakat Bima sebagai upaya memperkuat identitas keislaman dan menjaga harmoni sosial. Dengan menggunakan metode kualitatif deskriptif, penelitian dilakukan melalui studi lapangan dan analisis makna terhadap ungkapan-ungkapan tradisional yang terdapat dalam Nggusu Waru. Hasil penelitian menunjukkan bahwa setiap ungkapan mengandung nilai yang selaras dengan ajaran Islam. seperti, Maja Labo Dahu menumbuhkan kontrol moral melalui rasa malu dan takut; Ma Bae Ade menanamkan empati; Mambani Labo Disa menegaskan keberanian; Ma Lembo Ade ro Ma Na’e Sabar menekankan kesabaran; Ndinga Nggahi Rawi Pahu mengajarkan konsistensi antara ucapan dan tindakan; Ma Taho Hidi menekankan keseimbangan hidup; Dou Ma Wara Di Woha Dou memperkuat solidaritas sosial; serta Ntau Ro Wara menggarisbawahi kesejahteraan fisik maupun spiritual. Temuan ini menegaskan bahwa Islam dan budaya lokal Bima berinteraksi secara harmonis dan saling melengkapi dalam membentuk etika sosial, spiritual, dan budaya masyarakat. Penelitian ini memberikan penegasan bahwa ungkapan tradisional Bima merupakan manifestasi nyata integrasi nilai Islam dan kearifan lokal dalam kehidupan sehari-hari